Regulation of air-sea CO2 flux and aragonite saturation state in coral reef ecosystems along the eastern coast of Hainan Island, China - Wei Yang; Zijia Zheng; Peiqiang Zhuang; Jianhang Zhang; Wei Deng; Shengyong Li; Yanmei Liu; Ming He; Yingfeng Chen; Bingbing Yu; Xinxin Xu; Xinxing Li; et al. (Marine Pollution Bulletin, 2026)

Seismic Prediction of Shallow Unconsolidated Sand in Deepwater Areas - Jiale Chen; Yingfeng Xie; Tong Wang; Haoyi Zhou; Zhen Zhang; Yonghang Li; Shi Zhang; Wei Deng (Journal of Marine Science and Engineering, 2025)
Recently, shallow gas fields and hydrate-bearing sand in the deepwater area of the northern South China Sea have been successively discovered, and the accurate prediction of shallow sands is an important foundation. However, most of the current prediction methods are mainly for deep oil and gas reservoirs. Compared with those reservoirs with high degree of consolidation, shallow sandy reservoirs are loose and unconsolidated, whose geophysical characteristics are not well understood. This paper analyzes the logging data of shallow sandy reservoirs recovered in the South China Sea recently, which show that the sand content has a significant influence on Young’s modulus and Poisson’s ratio of the sediments. Therefore, this paper firstly constructs a new petrophysical model of unconsolidated strata targeting sandy content and qualitatively links the mineral composition and the elastic parameters of the shallow marine sediments and defines a new indicator for sandy content: the modified brittleness index (MBI). The effectiveness of MBI in predicting sandy content is then verified by measured well data. Based on pre-stack seismic inversion, the MBI is then inverted, which will identify the sandy deposits. The method proposed provides technical support for the subsequent shallow gas and hydrate exploration in the South China Sea.

Evaluating the impacts of drilling and extraction activities on the marine carbonate system in the natural gas fields of Beibu Gulf, Northern South China Sea - Minxia Zhang; Wei Yang; Jianhang Zhang; Chuqian Lu; Yingxu Wu; Peiqiang Zhuang; Yanmei Liu; Shasha Qi; Xing Chen; Wei Deng; Zijia Zheng; Ming He; et al. (Marine Environmental Research, 2025)

Multidimensional effects of green waste vermicomposting on cadmium contaminated soil ecosystems: From physicochemical properties to microbial communities - Li Huang; Yurui Meng; Boyou Pan; Bogui Pan; Junyu Wei; Jinhua Ding; Yingfeng Deng; Xianglan Su; Ziwei Yuan; Menghao Zhang (Journal of Hazardous Materials, 2024)

Estimation of Gas Hydrate Saturation Regarding the Hydrate Morphology in Hydrate-Bearing Sands in the Qiongdongnan Basin, South China Sea - Deng Wei; Liang Jinqiang; Kuang Zenggui; Xie Yingfeng; Yan Pin (Pure and Applied Geophysics, 2023)

Subduction hydrothermal regime and seismotectonic variation along Kermadec–Tonga megathrusts - Ye Zhu; Yingfeng Ji; Weiling Zhu; Rui Qu; Chaodi Xie; Deng Zeng (Journal of Asian Earth Sciences, 2023)